Intratumoral natural killer cells show reduced effector and cytolytic properties and control the differentiation of effector Th1 cells. (1st December 2016) - Paul, Sourav; Kulkarni, Neeraja; Shilpi,; Lal, Girdhari
ABSTRACT: Natural killer (NK) cells are known to have effector and cytolytic properties to kill virus infected or tumor cells spontaneously. Due to these properties, NK cells have been used as an adoptive cellular therapy to control tumor growth in various clinical trials but have shown limited clinical benefits. This indicates that our knowledge about phenotypic and functional differences in NK cells within the tumor microenvironment and secondary lymphoid tissues is incomplete. In this work, we report that B16F10 cell-induced melanoma recruits the CD11b + CD27 + subset of NK cells at a very early stage during tumor progression. These intratumoral NK cells showed increased expression of CD69, reduced inhibitory receptor KLRG1, and decreased proliferative ability. As compared to splenic NK cells, intratumoral NK cells showed decreased expression of activating receptors NKG2D, Ly49D and Ly49H; increased inhibitory receptors, NKG2A and Ly49A; decreased cytokines IFNγ and GM-CSF; decreased cytokine receptors IL-21R, IL-6Rα, and CD122 expression. Depletion of NK cells led to decrease peripheral as well as intratumoral effector CD4 + T-bet + cells (Th1), and increased tumor growth. Furthermore, purified NK cells showed increased differentiation of Th1 cells in an IFNγ-dependent manner. Anti-NKG2D in the culture promoted differentiation of effector Th1 cells. Collectively, these observations suggest that intratumoral NK cells possess several inhibitory functions that can be partly reversed by signaling through the NKG2D receptor or by cytokine stimulation, which then leads to increased differentiation of effector Th1 cells.